Convergence of Evidence Supports a Chuska Mountains Origin for the Plaza Tree of Pueblo Bonito, Chaco Canyon. Issue 2 (April 2020) - Guiterman, Christopher H.; Baisan, Christopher H.; English, Nathan B.; Quade, Jay; Dean, Jeffrey S.; Swetnam, Thomas W.
Abstract : The iconic Plaza Tree of Pueblo Bonito is widely believed to have been a majestic pine standing in the west courtyard of the monumental great house during the peak of the Chaco Phenomenon (AD 850–1140). The ponderosa pine ( Pinus ponderosa ) log was discovered in 1924, and since then, it has been included in "birth" and "life" narratives of Pueblo Bonito, although these ideas have not been rigorously tested. We evaluate three potential growth origins of the tree (JPB-99): Pueblo Bonito, Chaco Canyon, or a distant mountain range. Based on converging lines of evidence—documentary records, strontium isotopes ( 87 Sr/ 86 Sr), and tree-ring provenance testing—we present a new origin for the Plaza Tree. It did not grow in Pueblo Bonito or even nearby in Chaco Canyon. Rather, JPB-99 originated from the Chuska Mountains, over 50 km west of Chaco Canyon. The tree was likely carried to Pueblo Bonito sometime between AD 1100 and 1130, although why it was left in the west courtyard, what it meant, and how it might have been used remain mysteries. The origin of the Plaza Tree of Pueblo Bonito underscores deep cultural and material ties between the Chaco Canyon great houses and the Chuska landscape.